Oxygen permeability through internal oxidation zone in Fe–Cr alloys under dry and humid conditions at 973 and 1 073 K - Setiawan, Asep Ridwan; Ani, Mohd Hanafi; Ueda, Mitsutoshi; Kawamura, Kenichi; Maruyama, Toshio (The Iron and Steel Institute of Japan, 2010)
Internal oxidation of Fe–Cr alloys were investigated in dry and humid atmospheres at temperatures of 973 and 1 073 K in order to clarify the effect of humidity on the oxygen permeability in internal oxidation zone. The oxygen partial pressure in the chamber was fixed by Fe/FeO powder mixture. The calculated oxygen permeability increases linearly with increasing Cr concentration in the alloys, both at 973 and 1 073 K. Moreover, the presence of humidity enhanced the oxygen permeability compared with that under dry condition. The oxygen permeability through IOZ in humid atmosphere is larger than that in dry atmosphere as a factor of 1.2.